2014
DOI: 10.1364/josaa.31.000569
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of retinal vascular structure and perfusion with a nonconfocal adaptive optics scanning light ophthalmoscope

Abstract: Imaging of the retinal vascular structure and perfusion was explored by confocal illumination and nonconfocal detection in an adaptive optics scanning light ophthalmoscope (AOSLO), as an extension of the work by Chui et al. [Biomed. Opt. Express 3, 2537 (2012)]. Five different detection schemes were evaluated at multiple retinal locations: circular mask, annular mask, circular mask with filament, knife-edge, and split-detector. Given the superior image contrast in the reflectance and perfusion maps, the split-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…Our approach builds on earlier work from Elsner et al [9] who showed that the contrast of features obtained with a scanning laser ophthalmoscope could be enhanced by offsetting the confocal detection aperture, Chui and colleagues [10] incorporated this principle in an adaptive optics scanning laser ophthalmoscope (AOSLO) observing increased contrast at the blood vessel wall, and flowing blood cells within the vascular network. Sulai and colleagues [11] improved this method by blocking the center of the light distribution in the detector plane and capturing the remaining light to the left of the center in one detector, and the light to the right of center in another. By differencing the images from the two detectors, they were able to digitally remove light common to the two images, further increasing contrast in the final image.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach builds on earlier work from Elsner et al [9] who showed that the contrast of features obtained with a scanning laser ophthalmoscope could be enhanced by offsetting the confocal detection aperture, Chui and colleagues [10] incorporated this principle in an adaptive optics scanning laser ophthalmoscope (AOSLO) observing increased contrast at the blood vessel wall, and flowing blood cells within the vascular network. Sulai and colleagues [11] improved this method by blocking the center of the light distribution in the detector plane and capturing the remaining light to the left of the center in one detector, and the light to the right of center in another. By differencing the images from the two detectors, they were able to digitally remove light common to the two images, further increasing contrast in the final image.…”
Section: Introductionmentioning
confidence: 99%
“…1). In order to increase the vessel contrast in the SLO images an offset pinhole configuration or a split detector scheme has to be used [34,47]. The entire recorded data set can be viewed in Media 3.…”
Section: Resultsmentioning
confidence: 99%
“…This would offer the possibility to adjust the compromise between contrast and SNR in postdetection. Previous research have reported the use of annular apertures for narrow field of view (<30 deg) 13,[17][18][19][21][22][23] or the combination of information from differently shaped apertures for very narrow field of view (<1 deg); 20,23,24 our multimode implementation provides a wide-field capability (the native field of view of the SLO, of up to 200 deg) and high-contrast imaging simultaneously.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, an annular aperture offers the complementary function of recording only the scattered light, rejecting the direct backreflection contribution; this mode of operation is called indirect, scatter, dark-field, or Tyndall-mode. 8,10,11,13,[17][18][19][20] Several researchers have reported on the benefit provided by the use of different pinhole apertures as spatial filters, 13,[17][18][19][21][22][23] including multichannel imaging, 20,23,24 however, confocal imaging with small pinholes is limited to relatively small fields of view of <30 deg or an order-of-magnitude less than this for diffraction-limited imaging achievable with adaptive-optics correction. [25][26][27][28] The effect of optical aberrations on the image of the retina is much more severe than for the illuminating beam since image formation uses the whole pupil, so the numerical aperture for the imaging return path is typically 10 times greater than for the illuminating beam yielding commensurately higher levels of aberration.…”
Section: Introductionmentioning
confidence: 99%